2010
DOI: 10.1111/j.1651-2227.2010.01920.x
|View full text |Cite
|
Sign up to set email alerts
|

Exercise improves the ApoB/ApoA‐I ratio, a marker of the metabolic syndrome in obese children

Abstract: Training targeted at Fat max reduces the prevalence of metabolic syndrome and its associated factors in obese children. In particular, this intervention decreases the ApoB/ApoA-I ratio, which may be considered as a marker for following this syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(88 citation statements)
references
References 25 publications
2
80
1
3
Order By: Relevance
“…The main content of the programs was based on treadmills, cycle ergometers, rowers (machines) (23,28), sports games, such as soccer and basketball (21,22,26), running (21,26), walking (22,24,25), cycling, snowshoeing (22), and skipping rope (27,29). Finally, only four studies reported compliance (23,25,26,28), and all of them showed above 80%.…”
Section: Aerobic Exercise Program Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…The main content of the programs was based on treadmills, cycle ergometers, rowers (machines) (23,28), sports games, such as soccer and basketball (21,22,26), running (21,26), walking (22,24,25), cycling, snowshoeing (22), and skipping rope (27,29). Finally, only four studies reported compliance (23,25,26,28), and all of them showed above 80%.…”
Section: Aerobic Exercise Program Characteristicsmentioning
confidence: 99%
“…Finally, nine articles met all inclusion criteria and were used for the meta-analysis. Table 1 summarizes the study characteristics (21,22,23,24,25,26,27,28,29) (nZ191 and nZ176, in intervention and control groups respectively). Three studies were conducted in the USA (22,23,28), one in Germany (21), three in Korea (25,27), one in Tunisia (26), and one in Turkey (24).…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations